2014
DOI: 10.5935/0004-2749.20140071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of choroidal thickness in patients with obstructive sleep apnea/hypopnea syndrome

Abstract: Obstructive sleep apnea/hypopnea syndrome (OSAHS) is characterized by transient upper airway resistance caused by a recurrent reduction or cessation of airflow, due to partial or complete occlusion of the upper airway during sleep. It is associated with sleep fragmentation, arousals, bradycardia, tachycardia, and inadequate oxygen saturation despite an increased respiratory effort (1) . Major clinical consequences of the disorder include excessive daytime sleepiness, neurocognitive dysfunction, cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Using enhanced-depth imaging optical coherence tomography, Kara et al . demonstrated that subfoveal choroidal thickness was decreased in patients with moderate or severe OSAS 13 . Karalezli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Using enhanced-depth imaging optical coherence tomography, Kara et al . demonstrated that subfoveal choroidal thickness was decreased in patients with moderate or severe OSAS 13 . Karalezli et al .…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiologic standpoint, CSC and OSA are known to have opposing effects on CT, with CSC being associated with increased CT and OSA being associated with decreased CT. 10 -14 Prior studies have investigated CT in patients with CSC or OSA but have not addressed OSA treatment status and OSA severity as measured by overnight in-laboratory polysomnography, nor have important variables such as Oxygen Desaturation Index (ODI) or nocturnal oxygen saturation (SpO 2 ) nadir been evaluated. 15 -17 The ODI is a measure of hypoxemic burden during sleep secondary to OSA, and is defined as a 3% or more change in the number of oxygen desaturation events per hour of sleep (eg, a drop in nocturnal SpO 2 nadir from 99% to 95% would be considered an oxygen desaturation event). The use of these novel biometric features allows for a detailed characterization of OSA disease severity not previously leveraged in the ophthalmology literature but often described in the sleep medicine literature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in the literature have investigated the effect of Obstructive Sleep Apnea Syndrome (OSAS) on CT. 7 , 8 , 9 , 10 , 11 In a meta-analysis evaluating these studies, a decline in choroid thickness was found in the CT of patients with Obstructive Sleep Apnea (OSA). 12 It was argued that the enhancing effect of recurrent upper respiratory tract obstructions during sleep on sympathetic activity, hypoxia and hypercapnia resulted from deterioration of vascular circulation and choroidal blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hypoxia and hypercapnia due to NSD may affect the choroidal blood flow and may change the choroidal thickness. Although several studies have investigated CT in patients with OSAS, 7 , 8 , 9 , 10 , 11 to best of our knowledge there is no study investigating CT in patients with NSD. Therefore, in the present study, we aimed to evaluate the CT using EDI-OCT in MNSD patients.…”
Section: Introductionmentioning
confidence: 99%